Three-dimensional mapping of the greater palatine artery location and physiology - Qi, Baiyan; Khazeinezhad, Reza; Hariri, Ali; Yim, Wonjun; Jin, Zhicheng; Sasi, Lekshmi; Chen, Casey; Jokerst, Jesse V (Dento-maxillo-facial radiology, 2023)
To develop a novel technique for localizing and reconstructing the greater palatine artery (GPA) using three-dimensional (3D) technology. A miniaturized intraoral ultrasound transducer was used to imaging landmarks including the GPA, gingival margin (GM), and palatal masticatory mucosa (PMM). A 5-mm-thick solid hydrogel couplant was integrated to replace traditional ultrasound gel and avoid bubbles when moving the transducer. A panorama image provided the relative localization of landmarks including the GPA, PMM, and hard palate. Short- and long-axis imaging of GPA was performed in five subjects including 3D mapping of GPA branches and surrounding tissues in a volume of 10 mm × 8 mm × 10 mm. Full-mouth Doppler imaging was also demonstrated on both the dorsal and ventral tongue as well as buccal mucosa and sublingual region on two subjects. This study can measure the vertical distance from the GM to the GPA and depth from PMM to GPA and visualize the GPA localization in a 3D manner, which is critical to evaluate the available volume of palatal donor tissues and avoid sectioning of GPA during surgical harvesting of the tissues. Finally, the transducer's small size facilitates full-mouth Doppler imaging with the potential to improve the assessment, diagnosis, and management of oral mucosa.